2017
DOI: 10.5539/jel.v6n4p276
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Yoga on Spiritual Intelligence in Air Traffic Controllers of Tehran Flight Control Center

Abstract: The aim of this study was to evaluate the efficacy of yoga on spiritual intelligence in air traffic controllers in Tehran flight control center. This was a quasi-experimental research and the study population includes all air traffic controllers in Tehran flight control center. The sample consisted of 40 people of the study population that were selected through convenience sampling method and were randomly divided into experimental group (20) and control group (n=20). This research was conducted through traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… Pandya (2017) also reported an enhanced level of spiritual well-being, as well as increased levels of spiritual experiences (such as the feeling of deep inner peace and harmony, and proximity to the divine), aspirations, existential thinking, a development of an integrative worldview (i.e., the view that the reality is complex, namely both scientific and spiritual at the same time) ( Pandya, 2018 , 2019 ), and a decreased level of existential anxieties ( Pandya, 2018 ) after intense and holistic yoga programs. Another longitudinal study ( Safara and Ghasemi, 2017 ) found that yoga positively affected all aspects of spiritual intelligence (a construct that involves spiritual and intelligence structures ( Emmons, 2000 ), namely critical existential thinking, production of personal meaning, transcendental consciousness, and expanded state of consciousness. This result is supported by a cross-sectional study ( Seena et al, 2017 ), showing higher levels of spiritual intelligence in all dimensions among yoga practitioners compared with controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Pandya (2017) also reported an enhanced level of spiritual well-being, as well as increased levels of spiritual experiences (such as the feeling of deep inner peace and harmony, and proximity to the divine), aspirations, existential thinking, a development of an integrative worldview (i.e., the view that the reality is complex, namely both scientific and spiritual at the same time) ( Pandya, 2018 , 2019 ), and a decreased level of existential anxieties ( Pandya, 2018 ) after intense and holistic yoga programs. Another longitudinal study ( Safara and Ghasemi, 2017 ) found that yoga positively affected all aspects of spiritual intelligence (a construct that involves spiritual and intelligence structures ( Emmons, 2000 ), namely critical existential thinking, production of personal meaning, transcendental consciousness, and expanded state of consciousness. This result is supported by a cross-sectional study ( Seena et al, 2017 ), showing higher levels of spiritual intelligence in all dimensions among yoga practitioners compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, Smith et al (2011) found no difference between the integrated yoga group and the yoga as the exercise group; both of the yoga groups showed an increased level of hope compared with the no intervention control. Overviewing randomized control interventions, three papers reported almost null or partially positive findings ( Moadel et al, 2007 ; Danhauer et al, 2009 ; Lötzke et al, 2016 ), while four studies reported clear beneficial outcomes concerning spiritual experiences, spiritual intelligence, a level of hope, a sense of existence, presence, and awareness of body-mind connectedness ( Smith et al, 2011 ; Safara and Ghasemi, 2017 ; Wahlström et al, 2018 ; Pandya, 2019 ).…”
Section: Resultsmentioning
confidence: 99%